Nasoseptal perforations : endoscopic repair techniques - Alobid, Isam; Castelnuovo, Paolo (Thieme, 2017)
This atlas offers a complete review of all endoscopic approaches available for the repair of nasoseptal perforations, following damage that may occur through trauma, infection, drug abuse, or as a result of endoscopic skull base surgery. Approaches are explained step by step using brilliant photographs from fresh cadaver dissections. Full-color photos of fresh cadaver dissections illustrate all steps for each approach. Specific anatomic landmarks as revealed during each step are detailed, providing confidence in spatial orientation. Includes risks and potential complications as well as methods to reduce them. Videos of cadaver dissections and live surgery. -- Publisher.